2016
DOI: 10.2147/ott.s101310
|View full text |Cite
|
Sign up to set email alerts
|

The effects of miR-1207-5p expression in peripheral blood on cisplatin-based chemosensitivity of primary gallbladder carcinoma

Abstract: ObjectiveThe aim of this study was to investigate the association between miR-1207-5p expression in peripheral blood and the chemosensitivity of primary gallbladder carcinoma (PGBC).MethodsA total of 85 patients with PGBC undergoing preoperative chemotherapy were divided into effective (n=18) and ineffective (n=67) groups. Another 70 healthy individuals were selected as the control group. An miR-1207-5p mimic (mimic group), an inhibitor (inhibitor group), and a negative control (NC group) sequence were transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…MicroRNAs (miRNAs/miRs) are a class of non-coding small RNAs that bind to the 3'-untranslated region (3'-UTR) of mRNA to regulate mRNA expression (17)(18)(19). miRNAs have been proven to be involved in various cellular processes, including cell growth, differentiation and metabolic progression (20)(21)(22)(23)(24). The dysregulation of miRNAs has also been confirmed in AR, suggesting the potential function of miRNAs in AR (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are a class of non-coding small RNAs that bind to the 3'-untranslated region (3'-UTR) of mRNA to regulate mRNA expression (17)(18)(19). miRNAs have been proven to be involved in various cellular processes, including cell growth, differentiation and metabolic progression (20)(21)(22)(23)(24). The dysregulation of miRNAs has also been confirmed in AR, suggesting the potential function of miRNAs in AR (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…These reports suggest a potential oncogenic role of miR-1207 in cancer. Moreover, a previous report about the effects of miR-1207-5p expression in peripheral blood on cisplatin-based chemosensitivity in primary gallbladder carcinoma patients, indicating the lower miR-1207-5p expression in effective group than in the ineffective group after chemotherapy (26), suggesting its role in chemosensitivity. Therefore, the present study first detected the expression level of miR-1207-5p in normal MCF-10A cells and TNBC MDA-MB-436, MDA-MB-453 and MDA-MB-231 cell lines, and found that, compared with normal MCF-10A cells, there was a higher miR-1207-5p expression level in the TNBC cell lines, with the highest level being observed in the MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, lnc-RNA-MYLK-AS1 promotes GEM resistance by upregulating EZH expression 19. Other studies report that MiR-218-5p promotes GBC sensitivity to GEM by attenuating PRKCE expression 24,75. However, MiR-125b-5p enhances GBC sensitivity to cisplatin by downregulating Bcl-2 25,41.…”
Section: Epigenetics-involved Chemoresistance In Gbcmentioning
confidence: 99%
“… 19 Other studies report that MiR-218-5p promotes GBC sensitivity to GEM by attenuating PRKCE expression. 24 , 75 However, MiR-125b-5p enhances GBC sensitivity to cisplatin by downregulating Bcl-2. 25 , 41 GBC sensitivity to cisplatin was shown to increase when MiR-1207-5p expression decreased in the peripheral blood.…”
Section: Epigenetics-involved Chemoresistance In Gbcmentioning
confidence: 99%